2005
DOI: 10.1017/s1355617705050186
|View full text |Cite
|
Sign up to set email alerts
|

The influence of executive functions, sensation seeking, and HIV serostatus on the risky sexual practices of substance-dependent individuals

Abstract: From a public health standpoint, identifying factors that contribute to risky sexual practices among substance-dependent individuals is critical, particularly in the context of HIV infection. This study examines the respective contributions of executive neurocognitive functions, sensation seeking, and HIV serostatus in predicting risky sexual practices among poly-substance users (with a history of dependence primarily for cocaine or cocaine0heroin). HIV1 (n 5 109) and HIV2 (n 5 154) substance-dependent individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 75 publications
5
83
1
3
Order By: Relevance
“…SENSATION SEEKING Zuckerman (1994) defined sensation seeking as "a trait defined by the seeking of varied, novel, complex, and intense sensations and experiences, and the willingness to take physical, social risks, legal, and financial risks for the sake of such experience" (Zuckerman, 1994, p. 27). Sensation seeking has been identified as an important correlate of sexual risk behaviors (Bancroft et al, 2004;Crawford et al, 2003;Donohew et al, 2000;Gonzalez et al, 2005;Gullette & Lyons, 2005;Hoyle, Fejfar, & Miller, 2000;Kalichman, Cain, Zweben, & Swain, 2003;Kalichman, Heckman, & Kelly, 1996;Rolison & Scherman, 2003;Thompson, Kao, & Thomas, 2005) yet there is little information on gender differences in these relationships. Although, on average, men tend to be higher in sensation seeking than women (Bell, O'Neal, Feng, & Schoenrock, 1999;Gullette & Lyons, 2005;Zuckerman, 1994), many women are high sensation seekers and an increasing number of women take health risks such as binge drinking (Pirkle & Richter, 2006;Wechsler et al, 2002).…”
Section: Self Esteemmentioning
confidence: 99%
“…SENSATION SEEKING Zuckerman (1994) defined sensation seeking as "a trait defined by the seeking of varied, novel, complex, and intense sensations and experiences, and the willingness to take physical, social risks, legal, and financial risks for the sake of such experience" (Zuckerman, 1994, p. 27). Sensation seeking has been identified as an important correlate of sexual risk behaviors (Bancroft et al, 2004;Crawford et al, 2003;Donohew et al, 2000;Gonzalez et al, 2005;Gullette & Lyons, 2005;Hoyle, Fejfar, & Miller, 2000;Kalichman, Cain, Zweben, & Swain, 2003;Kalichman, Heckman, & Kelly, 1996;Rolison & Scherman, 2003;Thompson, Kao, & Thomas, 2005) yet there is little information on gender differences in these relationships. Although, on average, men tend to be higher in sensation seeking than women (Bell, O'Neal, Feng, & Schoenrock, 1999;Gullette & Lyons, 2005;Zuckerman, 1994), many women are high sensation seekers and an increasing number of women take health risks such as binge drinking (Pirkle & Richter, 2006;Wechsler et al, 2002).…”
Section: Self Esteemmentioning
confidence: 99%
“…Further, a community-based study showed that high scores in the BAS-RR and BAS-FS components are associated with the presence of a lifetime alcohol abuse disorder (25). Similarly sensation-seeking has been shown to be associated with psychopathy (26), substance abuse and dependence (27,28), alcohol abuse and dependence (29), substance dependence associated with major psychiatric disorders (30), pathological gambling (31) and motor vehicle accidents (31,32).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neither study assessed relationships among sexual risk behaviors and psychosocial, cognitive, behavioral, and physical health factors that are known to be related to risk taking behaviors in younger HIV-infected persons (Crepaz and Marks 2002;Gonzalez et al 2005) and that may predict risky sexual practices in older adults (e.g., Chesney et al 2003;Heckman et al 2002;Oursler et al 2006;Pitts et al 2005;Valcour and Paul 2006).…”
Section: Introductionmentioning
confidence: 99%